Climate risks, agricultural vulnerabilities and adaptation pathways in Nampula and Zambezia based on field evidence from Mozambique - Mwungu, Chris; Majambo, Gamoyo; Binge, Brenda; Chilambe, Pedro (2025)
This report examines climate risks, agricultural vulnerabilities, and adaptation pathways in the provinces of Nampula and Zambezia in Mozambique, where rural livelihoods heavily rely on smallholder farming. Increasing exposure to droughts, tropical cyclones, flooding, and heat stress has disrupted production, weakened value chains, and increased food insecurity. Using a mixed-methods approach, the study combines a thorough desk review with technical validation workshops, focus group discussions in Ribaue and Alto Molocue, and stakeholder consultations to evaluate climate hazards and local adaptive responses. Findings indicate that key crops such as maize, cassava, beans, rice, groundnuts, sesame, sorghum, cashew nuts, and bananas are affected by climate factors at all stages of the value chain, from input procurement to consumption. Farmers employ various on-farm and off-farm coping strategies, yet these remain inadequate due to limited access to financial resources, extension services, infrastructure, and institutional support. Despite government programmes and development partner initiatives aimed at adaptation, gaps remain in technical capacity, funding, and policy coherence, hampering effective implementation. The report highlights that building long-term resilience involves strengthening institutional coordination, enhancing climate information services, investing in climate-smart infrastructure, and fostering inclusive, community-led adaptation strategies. These measures are essential to protect livelihoods and promote sustainable agricultural development amid increasing climate change and variability.